Neutron and synchrotron X-ray diffraction for understanding crack tip mechanics - Kelleher, J F (My University, 2019)
The fatigue behaviour of polycrystalline metals is often studied through crack propagation analysis [1,2]. Nevertheless, understanding the mechanical processes that take place right at the crack tip [3,4] would also involve considering the deformation developing at the plastic zone and the contact between the crack faces over a portion of the loading cycle [5–7]. Paris law or newer models such as Forman equation are commonly used to interpret growth data [8], but cannot be used to generalise for complex loading scenarios, such as multiaxial loads [9–11] or variable amplitude loads [2]. Diffraction methods are a powerful tool to characterise crack tip strains and stresses [12]. The basics principles of neutron and synchrotron diffraction for measuring bulk properties are discussed [13,14], with special emphasis on grain size effects [15,16], transition between plane stress and plain strain conditions [17], measurement of the plastic zone and development of shielding effects at the crack tip [18]. REFERENCES [1] P. Lopez-Crespo, P.J. Withers, F. Yusof, H. Dai, A. Steuwer, J.F. Kelleher, T. Buslaps, Overload effects on fatigue crack-tip fields under plane stress conditions: surface and bulk analysis, Fatigue and Fracture of Engineering Materials and Structures. 36 (2013) 75–84. [2] B. Moreno, A. Martin, P. Lopez-Crespo, J. Zapatero, J. Dominguez, Estimations of fatigue life and variability under random loading in aluminum Al-2024T351 using strip yield models from NASGRO, International Journal of Fatigue. 91 (2016) 414–422. [3] C. Bathias, Retrospective view on the role of the plastic zone at a fatigue crack tip, Fatigue and Fracture of Engineering Materials and Structures. 19 (1996) 1301–1306. [4] P. Lopez-Crespo, D. Camas, F. V Antunes, J.R. Yates, A study of the evolution of crack tip plasticity along a crack front, Theoretical and Applied Fracture Mechanics. 98 (2018) 59–66.
Difracción de rayos X y difracción de neutrones en estudios de fatiga y fractura de materiales
Conferencia invitada de Joseph F Kelleher
Keywords: Materiales; structural integrity; residual stress measurement; synchrotron radiation; neutron diffraction; x-ray diffraction